Accuracy of the Chest Trauma Score (CTS) as a Predictor of Acute Respiratory Distress Syndrome (ARDS) in Blunt Chest Trauma Patients: Single Center Study at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Peter, Billy; Arie Hasiholan Lumban Tobing; Erial Bahar (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: Chest trauma is the third most common cause of death due to trauma worldwide, with a mortality rate reaching 60%. Chest Trauma Score (CTS) is a chest trauma assessment score that can predict patient complications and death, including acute respiratory distress syndrome (ARDS). This study aims to determine the relationship and assess the accuracy of CTS as a predictor of ARDS in patients with blunt chest trauma. Methods: Medical records of 32 patients with blunt chest trauma were analyzed. Subjects were assessed for CTS, with components including age, number of rib fractures, presence of bilateral rib fractures, and lung contusion. Data were divided into two groups, CTS<5 and CTS≥5. Data were analyzed to determine the relationship between CTS and ARDS. Results: 62.5% of subjects had CTS ≥5 and 37.5% had CTS<5. As many as 68.8% of subjects with blunt chest trauma experienced ARDS. Analysis using the Fischer Exact Test showed that there was a significant relationship (p<0.05) between the CTS value and ARDS. The sensitivity of this study was 77.3%, specificity 70%, positive predictive value 85%, negative predictive value 58.3%. Conclusion: Statistically there is a significant relationship between the chest trauma score and ARDS, so the chest trauma score is considered accurate as a predictor of ARDS in patients with blunt chest trauma.